Adaptive learning and monetary policy design - George W. Evans; Seppo Honkapohja (Bank of Finland, 2002)
We review the recent work on interest rate setting, which emphasizes the desirability of designing policy to ensure stability under private agent learning.Appropriately designed expectations based rules can yield optimal rational expectations equilibria that are both determinate and stable under learning.Some simple instrument rules and approximate targeting rules also have these desirable properties.We take up various complications in implementing optimal policy, including the observability of key variables and the required knowledge of structural parameters.An additional issue that we take up concerns the implications of expectation shocks not arising from transitional learning effects.
URN:NBN:fi:bof-20140807108
Keywords: E52; E31; D84; 330; commitment; interest rate setting; adaptive learning; stability; determinacy; expectations shocks